2015
DOI: 10.2166/wst.2015.080
|View full text |Cite
|
Sign up to set email alerts
|

The combination of coagulation, acid cracking and Fenton-like processes for olive oil mill wastewater treatment: phytotoxicity reduction and biodegradability augmentation

Abstract: Olive oil mill wastewater (OOMW) is one of the most important industrial wastewaters in the world due to high organic load and phenolic compounds. In this study, an integration of three processes including coagulation, acid cracking and Fenton-like was evaluated to treat OOMW. The performance of alum, ferric chloride and polyaluminum chloride was studied as coagulants. Among coagulants, ferric chloride showed the best results in comparison with the others. Coagulation process with FeCl3 removed 91.2% chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 22 publications
4
12
0
Order By: Relevance
“…It passed from charge neutralizationprecipitation mechanism to adsorption mechanism. These results were in agreement with Yazdanbakhsh et al (2015). In the same line, regarding the removal mechanisms of Al-based coagulants, Gregory and Duan (2001) reported that the positively-charged hydroxide precipitates act as destabilizing agents of organic compounds.…”
Section: Effect Of Phsupporting
confidence: 83%
See 2 more Smart Citations
“…It passed from charge neutralizationprecipitation mechanism to adsorption mechanism. These results were in agreement with Yazdanbakhsh et al (2015). In the same line, regarding the removal mechanisms of Al-based coagulants, Gregory and Duan (2001) reported that the positively-charged hydroxide precipitates act as destabilizing agents of organic compounds.…”
Section: Effect Of Phsupporting
confidence: 83%
“…The majority of the tested flocculants completely removed the TSS and reduced considerably the COD and the BOD 5 . In another study, combination of coagulation, acid cracking and Fentonlike process could result the phytotoxicity of final OMW to decrease (Yazdanbakhsh et al, 2015). Stoller and Chianese (2006a) proposed a treatment process comprising an initial coagulation flocculation with aluminium sulphate or aluminium hydroxide, followed by batch UF and NF in series with composite thin film spiral-wound membranes.…”
Section: Important Strategies For Omw Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with combination of two chemical processes were also tested in some works, particularly using coagulation-flocculation and/or acid cracking prior to different Fenton process. Michael et al [6] achieved a high COD removal (87%), while the polyphenolic fraction was eliminated using a solar photo-Fenton; Papaphilippou et al [42] used a UV lamp photo-Fenton and reduced COD and TP by 73% and 87%, respectively; Kiril Mert et al [48] obtained COD reduction of 93% and 95% to TP with Fenton reagent; Kilic et al, [44] achieved almost completely degradation of TOC, COD, and TP (99%); and Yazdanbakhsh et al, [51] achieved 98% of TP removal, improving biodegradability (biochemical oxygen demand (BOD 5 /COD ratio) from 0.14 to 0.83. This combination of processes may constitute a potential solution for purification of OMW.…”
Section: Olive Mill Wastewater Treatment By Aopsmentioning
confidence: 99%
“…It has been proven that advanced oxidation processes (AOPs) are a good choice for treating wastewaters which cannot be easily treated using biological processes. The basis of treatment in AOP processes is the production of active radicals such as hydroxyl radical (OH • ) (6). Photochemical processes are a branch of AOPs in which UV radiation activates chemical compounds to generate OH • radicals.…”
Section: Introductionmentioning
confidence: 99%